Communication as a social innovation strategy: Comunicar la innovación social - Córdova-Camacho, Jhoana; Altamirano-Benítez, Verónica; Victoria-Mas, Juan Salvador (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The article seeks to reveal as a result the role of social innovation communication in user behavior, if the user’s intention to consume a product or service changes when he/she knows that the company offering the good or service has implemented a social innovation practice. In order to respond to this objective, two hypotheses were formulated and tested through the application of a survey based on a convenience sample, which collected 300 responses throughout Latin America. The results obtained suggest that consumers in Latin America, in general, not only want to have more information available and accessible (both in terms of media accessibility and language), but also want to get involved, be heard, and be able to intervene in the community either on their own initiative or encouraged by brands and companies in general.